Factors associated with pregnancy-related anxiety among pregnant women attending antenatal care follow-up at Bedelle general hospital and Metu Karl comprehensive specialized hospital, Southwest Ethiopia - Tarafa, Hunde; Alemayehu, Yadeta; Nigussie, Meskerem (Frontiers in Psychiatry, 2022)
Background: Pregnancy-related anxiety (PRA) is anxiety about the pregnancy, including labor and delivery, the health of the fetus or infant, the health of the mother, the accessibility and quality of healthcare resources, and/or the ability to parent. There is scarce evidence about the magnitude of pregnancy-related anxiety and its associated factors among pregnant women in Ethiopia. Therefore, this study aimed to assess the prevalence of pregnancy-related anxiety and its associated factors among pregnant women attending ANC follow-up at Bedelle general hospital and Mettu Karl comprehensive specialized hospital, Southwest Ethiopia. Methods: A hospital-based cross-sectional study was conducted among pregnant women attending ANC follow-up at Bedelle general hospital and Mettu Karl comprehensive specialized hospital. Data were collected from 406 sampled pregnant women who were selected through a systematic random sampling technique. Pregnancy-Related Anxiety Questionnaire-Revised (PRAQ-R2) was used to measure the outcome variable. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 26. Bivariate and multivariate logistic regression analyses were done to identify factors associated with pregnancy-related anxiety. Variables with P-value <0.05 were considered statistically significant. Results: The overall prevalence of pregnancy-related anxiety in this study was 32.7%. There was a positive and independent association between pregnancy-related anxiety and young age AOR= 2.14, 95% CI [1.49, 2.83], low income AOR= 2.01,95% CI [1.29, 3.14], poor social support AOR= 1.79, 95% CI [1.14, 3.37], high perceived stress AOR= 2.39, 95% CI [1.54, 3.62], depression AOR= 2.09, 95% CI [1.39, 2.89], and unwanted pregnancy AOR= 2.77, 95% CI [1.71, 4.54]. Conclusion: The findings of this study showed that the prevalence of pregnancy-related anxiety was high in the sampled pregnant women of Bedelle general hospital and Mettu Karl comprehensive specialized hospital. Pregnancy-related anxiety was positively associated with young age, low income, poor social support, high perceived stress, depression, and unwanted pregnancy. This finding suggests that clinicians should integrate screening for pregnancy-related anxiety into clinical standards. More efforts should be made in the future to reduce the anxiety among pregnant women who had an unwanted pregnancy, young women, and those with poor social support.